Analysis of polyester/wood composite fiber needling mat sound absorption performance. Issue 11 (5th July 2017) - Dong, Wang; Limin, Peng; Feng, Fu; Meihong, Liu; Boqi, Song
Abstract : The use of natural fibers in the manufacturing of sound absorbing materials has received much attention as a strategy to increase environment‐protection performance. In this study, the sound absorption property of a polyester/wood composite fiber needling mat (PWFM) was investigated by the Delany–Bazley (D‐B) model, phenomenon model (PM), and impedance tube. The applicability of those models and the effects of the parameters of the PWFM on sound absorption were analyzed. The results showed that the PM and D‐B models adequately predicted the sound absorption property of the PWFM. However, the discrepancies between the measurement and theoretical values were larger for lower density PWFWs. The accuracy of wood fiber diameter and the wood fiber morphology were significant determinants of the usability of those models. The sound absorption performance for PWFM increased with increased flow resistivity and density. The wood fiber surface roughness and small cracks played important roles in the improvement of the sound absorption characteristics of the PWFM. POLYM. COMPOS., 39:3823–3830, 2018. © 2017 Society of Plastics Engineers